Chapter 15. Root Crop Production - Julien Beuzelin; Peter J. Dittmar; Bonnie Wells; Johan Desaeger; Lincoln Zotarelli; Shouan Zhang; Qingren Wang; Craig Frey; Anna Meszaros (EDIS)
Chapter 15 of the Vegetable Production Handbook of Florida